DETERMINANTS OF FINANCIAL LITERACY OF MADURA ISLAND FARMERS HOUSEHOLDS: ORDERED PROBIT REGRESSION ANALYSIS - Dian Eswin Wijayanti; Moh. Wahyudi Priyanto; Aminah Happy Moninthofa Ariyani; Setiani Setiani (WIRATANI, 2026)
The constraints of low financial literacy result in limited access to financial products and services, suboptimal financial management, and increased vulnerability to financial risks. This low level of financial literacy can hinder the economic progress and well-being of farmer households. This study aims to identify the determinants of financial literacy among farmer households on Madura Island. The research location was selected because it is known to have a low level of financial knowledge. A simple random sampling method was employed, yielding a sample of 123 households. Financial literacy was divided into three variables: knowledge, skills, and behavior. The results of the ordered probit regression analysis indicate that the variables positively influencing knowledge, skills, and behavior are age, education, income, access to credit, government assistance, and membership in farmer groups. Age negatively affects financial skills and behavior, while education positively influences financial knowledge. Household income has a significant positive effect on all dimensions of financial literacy, indicating the importance of improving the economic capacity of farmers. Conversely, membership in farmer groups has a negative effect on financial literacy, suggesting that the activities of these groups have not been optimal in enhancing their members' financial capacity. Additionally, government assistance without accompanying financial education has a negative impact on financial skills. These findings emphasize the need for educational interventions based on financial literacy that are more contextual and integrated with farmer empowerment programs. This study makes an important contribution to the literature on financial literacy in the agricultural sector and provides strategic recommendations for designing programs to improve the financial capacity of farmers in underdeveloped regions.